Candy Cane Compared With Boot Stirrups in Vaginal Surgery: A Randomized Controlled Trial. Issue 11 (November 2020) - Gupta, Ankita; Meriwether, Kate; Tuller, Molly; Sekula, Michael; Gaskins, Jeremy; Stewart, J. Ryan; Hobson, Deslyn; Cardenas-Trowers, Olivia; Francis, Sean
Abstract : (Abstracted from Obstet Gynecol 2020;136:333–341) Incorrect patient positioning during surgery can lead to both transient and long-term injuries that affect patient recovery. Concerns about the role of patient positioning in neurologic injuries after gynecologic surgery have been raised in previous studies, especially the role of candy cane stirrups compared with boot stirrups.